Enhancing the Competitiveness of PT. Len Industri (Persero) through Human Resource Readiness to Support the Development of Defense and Security Equipment Mobility in the Era of Industry 4.0 - Novan Risnawan; Erzi Agson Gani; Imanuel Dindin; Ansori Ansori; Gita Amperiawan; Sumaryadi Sumaryadi; Suciati Suciati; Absaralita Sabarati; Mohtar Suyitno (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to analyze the improvement of PT. LEN Industri's (Persero) competitiveness through the readiness of human resources to support the development of defence and security equipment locomotion in the fourth industrial revolution era. The method used in this research is data collection through questionnaire distribution and literature study. The respondents in this research are PT employees. LEN Industri (Persero) who are involved in the development of defence and security equipment locomotion. The analysis results show that most respondents are ready to face the fourth industrial revolution, but there are still obstacles to using digital platforms—improving PT. LEN Industri's (Persero) competitiveness can be achieved by enhancing the readiness of human resources to adopt new technologies such as the Internet of Things (IoT), Big Data, Cloud Computing, Artificial Intelligence (AI), and Digital Twin. In conclusion, this research recommends PT. LEN Industri (Persero) to further enhance and manage its human resources to be better prepared to increase competitiveness in the fourth industrial revolution era.